Middlemen: A Directed Search Equilibrium Approach - Makoto Watanabe (Tinbergen Institute, 2012)
This paper studies an intermediated market operated by middlemen with high inventory holdings. I present a directed search model in which middlemen are less likely to experience a stockout because they have the advantage of inventory capacity, relative to other sellers. The model explains why popular items are sold at a larger premium, and everyday items at a larger discount, by large-scaled intermediaries. The concentration of middlemen's market, i.e., few middlemen, each with large capacity, can lead to a higher matching efficiency, but with a lower total welfare, compared to having many middlemen, each with small capacity.
Keywords: D4; F1; G2; L1; L8; R1; 330; Directed Search; Intermediation; Inventory holdings; Marktmechanismus; Suchtheorie; Matching; Theorie